Population dynamics of Aceria guerreronis Keifer (Acari: Eriophyidae) and associated predators on coconut fruits in Northeastern Brazil - Reis, A.C.; Gondim, M.G.C.; Moraes, G.J.; Hanna, R.; Schausberger, P.; Lawson-Balagbo, L.E.; Barros, R. (Springer, 2008)
Aceria guerreronis Keifer can cause severe damage to coconuts in several countries around the world. Rare studies have been conducted to determine the predatory mites associated with A. guerreronis in Brazil. The study evaluated the prevalence of A. guerreronis and associated predators on the bracts and on the surface of the fruits underneath the bracts, for 12 months, on coconut palms grown along the coast of the States of Alagoas, Paraíba and Pernambuco, Northeastern Brazil. Mites of 10 families were found, but by far the most abundant species was A. guerreronis, corresponding to 99.5% of the mites collected. The prevailing species amongst the predators were the Phytoseiidae mites Neoseiulus baraki (Athias-Henriot) and Neoseiulus paspalivorus (De Leon). These are flat mites that have short limbs, characteristics that allow them to invade the main habitat occupied by A. guerreronis. Other predators were found, but in low numbers, due mainly to their difficulty in reaching the fruit areas most inhabited by A. guerreronis. However, these mites could prey on that pest when it leaves its preferred habitat to disperse. No significant correlations were observed between the levels of abiotic factors and the population levels of A. guerreronis or of the phytoseiids associated with it. This probably occurred due to the simultaneous and conflicting effects of those factors on the mites in the field, or to significant differences between the climatic factors measured in the environment and those prevailing in the habitat occupied by A. guerreronis.